PRESTASI BELAJAR SISWA SEKOLAH DASAR DI DUKUH NGLAWU KABUPATEN SUKOHARJO PADA PEMBELAJARAN TERBATAS DI MASA PANDEMI DITINJAU DARI PERHATIAN ORANG TUA DAN KEMANDIRIAN BELAJAR - Retno Vina Kusuma Dianty; Abdul Rahman Abdul Rahman; Yuhastina Yuhastina (STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
This study aimed to determine the effect of parental attention and learning independence on the achievement of elementary school students during limited learning the Covid-19 pandemic. The approach of this study was quantitative correlation research with ex post facto type. The subject of this study were 110 elementary school students in Nglawu (name of a village). The sample used was 86 respondents who were selected using a proportional sampling technique with the Slovin Formula. Questionnaires, documentation, and observation were used as the instruments to collect the data. This data collected with Product Moment Correlation Test and Multiple regression test. Based on the results of the multiple regression test showed the equation model Y =34,817 + 0,231 X1 + 0,429 X2. The results of the correlation coefficient test showed that : (1) There was an influence between parental attention with student’s achievement (rcount > rtable = 0.527 > 0.2096; significance value 0.000 rtable) = 0.612 > 0.2096; significance value (0.000 < 0.05); (3) There was an influence between parental attention and independent learning together with student’s achievement (Rxy > Rtable) = 0.622 > 0.2096; the value of Sig F Change was (0.000 < 0.05).